Serum granulysin levels as a predictor of serious telaprevir‐induced dermatological reactions. Issue 8 (15th October 2014) - Suda, Goki; Yamamoto, Yoshiya; Nagasaka, Astushi; Furuya, Ken; Kudo, Mineo; Chuganji, Yoshimichi; Tsukuda, Yoko; Tsunematsu, Seiji; Sato, Fumiyuki; Terasita, Katsumi; Nakai, Masato; Horimoto, Hiromasa; et al.
<x xml:space="preserve">Abstract</x> Aim Telaprevir‐based therapy for chronic hepatitis C patients is effective; however, the high prevalence of dermatological reactions is an outstanding issue. The mechanism and characteristics of such adverse reactions are unclear; moreover, predictive factors remain unknown. Granulysin was recently reported to be upregulated in the blisters of patients with Stevens–Johnson syndrome (SJS). Therefore, we investigated the risk factors for severe telaprevir‐induced dermatological reactions as well as the association between serum granulysin levels and the severity of such reactions. Methods A total of 89 patients who received telaprevir‐based therapy and had complete clinical information were analyzed. We analyzed the associations between dermatological reactions and clinical factors. Next, we investigated the time‐dependent changes in serum granulysin levels in five and 14 patients with grade 3 and non‐grade 3 dermatological reactions, respectively. Results Of the 89 patients, 57 patients had dermatological reactions, including nine patients with grade 3. Univariate analysis revealed that grade 3 dermatological reactions were significantly associated with male sex. Moreover, serum granulysin levels were significantly associated with the severity of dermatological reactions. Three patients with grade 3 dermatological reaction had severe systemic manifestations including SJS, drug‐induced hypersensitivity syndrome, and systemic lymphoid swelling and high‐grade fever; all were hospitalized. Importantly, among the three patients, two patients' serum granulysin levels exceeded 8 ng/mL at onset and symptoms deteriorated within 6 days. Conclusion Male patients are at high risk for severe telaprevir‐induced dermatological reactions. Moreover, serum granulysin levels are significantly associated with the severity of dermatological reactions and may be a predictive factor in patients treated with telaprevir‐based therapy.